Digital Fairy Tales: Children's Literacy Development During the Covid-19 Pandemic - Ni Putu Sinta Dewi; Sugito (Universitas Pendidikan Ganesha, 2022)
Digital technology has become a part of most children's everyday experiences. In kindergarten, they tend to have many encounters with various forms of digital communication. The application of digital literacy in early childhood education is currently in the form of developing digital books and digital fairy tales. The purpose of this study is to describe and analyze the practice of developing digital fairy tales carried out in schools. This research uses the case study research method. The subjects of this study were 10 early childhood education teachers who became facilitators of digital fairy tale development. The selection of this subject was based on purposive sampling, with the consideration that the abilities and contributions of the informants could contribute to the understanding of the phenomenon under study. Data collection was carried out by in-depth interviews conducted through face-to-face meetings. Data analysis uses three types of activities, namely data reduction, data modeling, and drawing conclusions. The results of this study illustrate that the implementation of digital fairy tales and their development tend to lead to the application of digital fairy tale videos without direct interaction with early childhood. This application is not in accordance with the concepts and theories of digital literacy and digital fairy tales for early childhood. Thus, it is hoped that the development of digital fairy tales will take the point of view of the need for an important and more meaningful stimulus in early childhood without eliminating the interactions that are the core of storytelling activities.